Technological study of preparing gel from semi-solid extract of Cacalia hastata L. - D Jambaninj; Syed Azhar Syed Sulaiman; Syed Wasif Gillani; T S Davaasuren; G Erdenetsetseg; D Dungerdorj (Wolters Kluwer Medknow Publications, 2012)
Most of the drugs which are used for wound healing are imported in Mongolia. It is required to develop drug formulation and increase local productions used for the treatment of wound healing. For the purpose of solving the above problems, we aimed to prepare new drug formulation from Cacalia hastata L. for the treatment of wound healing. Cacalia hastata L. is a medicinal plant, member of the family Asteraceae. Cacalia hastata L. is widely used for the Mongolian traditional medicine to treat wound healing, gastric ulcer, poisoning fever, liver fever, bile fever, oral cavity, and gynecological diseases. We prepared Cacalia gel from semi-solid extract of Cacalia hastata L. using various excipients such as gel former, solvent, neutralizer, antimicrobial preservative, and humectant. Gel formulation was standardized by such criteria, as the amount of biologically active compound, appearance (color, smell), pH, viscosity, and bacterial contamination. Stability testing of gel formulation was studied by long-term method. The quality of the Cacalia gel which was stored in room temperature, its appearance, viscosity, and amount of biological active compound were stable. The stability testing of the gel formulation from Cacalia hastata L. is continued.